The Influences of the Gender Equality to the Local Economic Development (Case Study in Muko Muko District, Bengkulu Province, Indonesia, 2010-2019) - Handoko Hadiyanto (Budapest International Research and Critics University, 2021)
The objectives of this research is to know the influence of the gender equality in education, health and employment to the local economy in Muko Muko district, Bengkulu Province, Indonesia (period of 2010-2019). Models estimated using regresion. Secondary data was use in this research, some data from BPS (Central Statistic Office) Bengkulu Province, and also the collect of the data were observation and documentation. Data were analyzed using descriptive statistics and multiple regression. The result of the research shows that the gender equality in education, health and employment affair was positive impact on the local economics of Muko Muko district. Access discrimination to the women on education, health and employment can obstruct to local economic development. More than on economic purpose, gender equality was part of on honor to humanrights and also was a society empowerment for both men and women to obtain equality of acces to participation and possess to control and the equality of motivate in development.